The IASLC Lung Cancer Staging Project: Background Data and Proposals for the Classification of Lung Cancer with Separate Tumor Nodules in the Forthcoming Eighth Edition of the TNM Classification for Lung Cancer. Issue 5 (May 2016) - Detterbeck, Frank C.; Bolejack, Vanessa; Arenberg, Douglas A.; Crowley, John; Donington, Jessica S.; Franklin, Wilbur A.; Girard, Nicolas; Marom, Edith M.; Mazzone, Peter J.; Nicholson, Andrew G.; Rusch, Valerie W.; Tanoue, Lynn T.; et al.
ABSTRACT : Introduction: : Separate tumor nodules with the same histologic appearance occur in the lungs in a small proportion of patients with primary lung cancer. This article addresses how such tumors can be classified to inform the eighth edition of the anatomic classification of lung cancer. Separate tumor nodules should be distinguished from second primary lung cancer, multifocal ground glass/lepidic tumors, and pneumonic‐type lung cancer, which are addressed in separate analyses. Methods: : Survival of patients with separate tumor nodules in the International Association for the Study of Lung Cancer database were analyzed. This was compared with a systematic literature review. Results: : Survival of clinically staged patients decreased according to the location of the separate tumor nodule relative to the index tumor (same lobe > same side > other side) in N0 and N‐any cohorts (all M0 except possible other‐side nodules). However, there was also a decrease in the proportion of patients resected; among only surgically resected or among nonresected patients no survival differences were noted. There were no survival differences between patients with same‐lobe nodules and those with other T3 tumors, between patients with same‐side nodules and those with T4 tumors, and patients with other‐side nodules and those with other M1a tumors. The data correlated with those identified in a literature review. Conclusions: : Tumors with same‐lobe separate tumor nodules (with the same histologic appearance) are recommended to be classified as T3, same‐side nodules as T4, and other‐side nodules as M1a. Thus, there is no recommended change between the seventh and eighth edition of the TNM classification of lung cancer.